Berberine Alleviate Cisplatin-Induced Peripheral Neuropathy by Modulating Inflammation Signal via TRPV1 - Meng, Jing; Qiu, Siyan; Zhang, Ling; You, Min; Xing, Haizhu; Zhu, Jing (Frontiers in Pharmacology, 2022)
Cisplatin induced peripheral neuropathy (CIPN) is a severe neurodegenerative disorder caused by chemotherapy drugs. Berberine is a natural monomer compound of Coptis chinensis, which has anti-tumor effect and can improve neuropathy through anti-inflammatory. Transient receptor potential vanilloid (TRPV1) can sense noxious thermal and chemical stimuli, which is an important target for the study of pathological pain. In vivo and in vitro CIPN models, we found that berberine alleviated peripheral neuropathy associated with dorsal root ganglia inflammation induced by cisplatin. We confirmed berberine mediated the cisplatin induced neuroinflammatory reaction by inhibiting the overexpression of TRPV1 and NF-κB and activating the JNK/p38 MAPK pathways in early injury, which inhibited the expression of p-JNK and mediated the expression of p38 MAPK/ERK in late injury in vivo. Moreover, genetic deletion of TRPV1 significantly reduced the protective effects of berberine for mechanical and heat hyperalgesia in mice. After TRPV1 gene was knockout, the expression of NF-κB increased in late stage, and berberine inhibited the overexpression of NF-κB and p-ERK in late injury in vivo. Our results support berberine can reverse neuropathic inflammatory pain response induced by cisplatin, TRPV1 may be involved in this process.